Current Status of Oseltamivir Application and Its Future Development Trend - Wang, Yixin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Influenza is a common respiratory disease with severe complications that can be fatal in severe cases. Oseltamivir is a drug that suppresses influenza disease, it can effectively reduce the symptoms of influenza patients but there are also some adverse effects that can affect the quality of life of patients and the psychological status of the treatment process.  This article examines the side effects, mechanism of action, trends, and future prospects of oseltamivir, and draws conclusions about the drug's use in treating influenza. It provides direction and reference information for future research on this drug, discusses the limitations of its therapeutic efficacy and the challenges it will face. Liver enzyme levels should be carefully monitored and liver health should be carefully assessed when using oseltamivir to treat illnesses such as influenza. These studies will help provide better options for the treatment of diseases such as influenza. However, this paper has not addressed the limitations of whether oseltamivir has additional adverse effects in patients with hepatic and renal disorders, whether they can take the drug normally, and whether the dosage needs to be reduced compared to normal patients. In addition, even though oseltamivir is very effective against the influenza virus, it is not a perfect solution to all problems. It still has limitations and challenges to overcome in terms of viral suppression. In future studies, a deeper understanding of the mechanism of action, efficacy and safety of oseltamivir is needed to develop better anti-influenza drugs to serve patients.